Ecosystem transplant from a healthy reef boosts coral health at a degraded reef - Levy, Natalie; Marques, Joseane A.; Simon-Blecher, Noa; Bourne, David G.; Doniger, Tirza; Benichou, Jennifer I. C.; Lim, Jin Yan; Tarazi, Ezri; Levy, Oren (Nature communications, 2024)
Organismal communities associated with coral reefs, particularly invertebrates and microbes, play crucial roles in ecosystem maintenance and coral health. Here, we characterized the organismal composition of a healthy, non-urbanized reef (Site A) and a degraded, urbanized reef (Site B) in the Gulf of Eilat/Aqaba, Red Sea to assess its impact on coral health and physiology. Biomimetically designed terracotta tiles were conditioned for 6 months at both sites, then reciprocally transplanted, and scleractinian coral species, Acropora eurystoma and Stylophora pistillata , were attached for an additional 6 months. After 12 months, tiles from Site A transplanted to Site B exhibited greater invertebrate richness and diversity than Site B’s original tiles (via Cytochrome c. Oxidase subunit I metabarcoding). Key bacteria from the healthy reef were more prevalent on Site A tiles and on the tiles transplanted to Site B (via 16S rRNA gene sequencing). Corals originally from Site B attached to transplanted healthy tiles (Site A) showed higher photochemical capacity, increased endosymbionts, and reduced physiological stress, measured by total antioxidant capacity and an integrated biomarker response. Our findings demonstrate the successful transfer of organismal communities between reefs, highlighting the potential benefits of healthy reef-associated invertebrates and microbes on coral physiology and their implications for reef restoration strategies. Invertebrate and microbe communities support reef ecosystems and coral health. Here, the authors characterize these communities from degraded and healthy reefs, showing that transplanting these healthy communities improved coral health at degraded reefs.